Experiences with Macroprudential Policy-Five Case Studies - Darbar, Salim (IMF Working Papers; Working Paper ;, 2015)
This paper presents case studies of macroprudential policy in five jurisdictions (Hong Kong SAR, the Netherlands, New Zealand, Singapore, and Sweden). The case studies describe the institutional framework, its evolution, the use of macroprudential tools, and the circumstances under which the tools have been used. The paper shows how macroprudential policy is conducted under a heterogeneous set of institutional frameworks. In all cases macroprudential tools have been used to address risks in the housing market. In addition, some of them have moved to enhance the resilience of their banks to more general cyclical and structural risks.